A review of quantitative studies of South African youth resilience: Some gaps - van Rensburg, Angelique; Theron, Linda; Rothmann, Sebastiaan (South African Journal of Science, 2015)
Resilience (positive adjustment to hardship) relies on a socioecologically facilitated process in which individuals navigate towards, and negotiate for, health-promoting resources, and their social ecology, in return, provides support in culturally aligned ways (Ungar, Trauma Violence & Abuse 2013;14(3):255–266). In the light of international critiques of the conceptualisation and measurement of resilience, the aim of this study was to systematically review quantitative studies of South African youth resilience in order to consider to what extent such studies failed to address documented critique (Luthar et al., Child Development 2000;71(3):543–562). We argue that, for the most part, quantitative studies of South African youth resilience did not mirror international developments of understanding resilience as a complex socioecologically facilitated process. Furthermore, the majority of reviewed studies lacked a culturally or contextually sound measurement and contained conflicting operationalisations of resilience-related constructs. Essentially, the results of this study call for quantitative studies that will statistically explain the complex dynamic resiliencesupporting transactions between South African youth and their contexts and guide mental health practitioners and service providers towards more precise explanations and promotion of resilience in South African youth.